Prevention of age‐related neuromuscular junction degeneration in sarcopenia by low‐magnitude high‐frequency vibration - Bao, Zhengyuan; Cui, Can; Liu, Chaoran; Long, Yufeng; Wong, Ronald Man Yeung; Chai, Senlin; Qin, Ling; Rubin, Clinton; Yip, Benjamin Hon Kei; Xu, Zhihong; Jiang, Qing; Chow, Simon Kwoon‐Ho; et al. (Aging cell, 2024)
Neuromuscular junction (NMJ) degeneration is one of pathological factors of sarcopenia. Low‐magnitude high‐frequency vibration (LMHFV) was reported effective in alleviating the sarcopenia progress. However, no previous study has investigated treatment effects of LMHFV targeting NMJ degeneration in sarcopenia. We first compared morphological differences of NMJ between sarcopenic and non‐sarcopenic subjects, as well as young and old C57BL/6 mice. We then systematically characterized the age‐related degeneration of NMJ in SAMP8 against its control strain, SAMR1 mice, from 3 to 12 months old. We also investigated effects of LMHFV in SAMP8 on the maintenance of NMJ during the onset of sarcopenia with respect to the Agrin‐LRP4‐MuSK‐Dok7 pathway and investigated the mechanism related to ERK1/2 signaling. We observed sarcopenic/old NMJ presented increased acetylcholine receptors (AChRs) cluster fragmentation and discontinuity than non‐sarcopenic/young NMJ. In SAMP8, NMJ degeneration (morphologically at 6 months and functionally at 8 months) was observed associated with the sarcopenia onset (10 months). SAMR1 showed improved NMJ morphology and function compared with SAMP8 at 10 months. Skeletal muscle performance was improved at Month 4 post‐LMHFV treatment. Vibration group presented improved NMJ function at Months 2 and 6 posttreatment, accompanied with alleviated morphological degeneration at Month 4 posttreatment. LMHFV increased Dok7 expression at Month 4 posttreatment. In vitro, LMHFV could promote AChRs clustering in myotubes by increasing Dok7 expression through suppressing ERK1/2 phosphorylation. In conclusion, NMJ degeneration was observed associated with the sarcopenia onset in SAMP8. LMHFV may attenuate NMJ degeneration and sarcopenia progression by increasing Dok7 expression through suppressing ERK1/2 phosphorylation. In the sarcopenic SAMP8 model, NMJ degeneration preceded the onset of sarcopenia. LMHFV attenuated NMJ degeneration and sarcopenia progression by increasing Dok7 expression through suppressing ERK1/2 phosphorylation in skeletal muscle.